2010
DOI: 10.4103/0970-0358.70724
|View full text |Cite
|
Sign up to set email alerts
|

Post-burn scars and scar contractures

Abstract: The mortality and morbidity from burns have diminished tremendously over the last six to seven decades. However, these do not truly reflect whether the victim could go back to society as a useful person or not and lead a normal life because of the inevitable post-burn scars, contractures and other deformities which collectively have aesthetic and functional considerations. This article gives an overview of the post-burn scars and scar contractures, especially their prevention, minimisation and principles of ma… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
82
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 121 publications
(84 citation statements)
references
References 13 publications
2
82
0
Order By: Relevance
“…This is contrary to other studies which advocate for the release of the contracture after one year [10, 11]. The waiting period of one year is supposedly to allow the post-burn scar to mature, which is said to reduce the recurrence rate.…”
Section: Discussionmentioning
confidence: 74%
See 1 more Smart Citation
“…This is contrary to other studies which advocate for the release of the contracture after one year [10, 11]. The waiting period of one year is supposedly to allow the post-burn scar to mature, which is said to reduce the recurrence rate.…”
Section: Discussionmentioning
confidence: 74%
“…Just as the inappropriate management of burns leads to the occurrence of PBC, inadequate management of PBC leads to their recurrence [1, 9, 10]. Recurrence has been reported in developed and developing countries following both surgical and non-surgical management [7–9].…”
Section: Introductionmentioning
confidence: 99%
“…These contractures are commonly dealt in a separate sitting. [10] With regards to treatment, 60% (N=32) of the patients under went scar excision and SSG. For all the patients with linear band contracture(N=6) multiple z plasty was done .…”
Section: Discussionmentioning
confidence: 99%
“…7 Studies have shown severe functional limitations and disfigurement from scars and have demonstrated the need to promptly and adequately treat burn wounds to prevent contractures from forming. [8][9] Chest contractures have also arisen iatrogenically from breast augmentation and reconstruction. [10][11] Regardless of the etiology, chest contractures (and contractures in general) cause multiple complications, and their treatment and prevention is important.…”
Section: Discussionmentioning
confidence: 99%